Performance of rocket data communication system using wire rope isolator on sounding rocket RX - Rahardiyanti, Kandi; Laksono, Shandi Prio; Hakim, Khaula Nurul; Nugroho, Yuniarto Wimbo; Adi, Andreas Prasetya; Salman, Salman; Kurdianto, Kurdianto (Institute of Advanced Engineering and Science, 2025)
The rocket experiment (RX) ballistic rocket requires a reliable data communication system capable of withstanding intense vibrations and shocks during flight. This study investigates the application of wire rope isolators (WRI) to damper mechanical disturbances and protect the rocket's communication system. Installation of WRI position and direction in this experiment with compression position. A series of vibration tests were conducted using 4 WRI installed in the rocket’s 30 kg data communication compartment, vibration test results frequency between 4 Hz and 1500 Hz with acceleration of 8.37 g to 20.37 g, higher